Additional file 1 of Elevated ganglioside GM2 activator (GM2A) in human brain tissue reduces neurite integrity and spontaneous neuronal activity - Yi‐Chen Hsieh; Joseph Negri; Amy He; Richard V. Pearse; Lei Liu; Duc M. Duong; Lori B. Chibnik; David A. Bennett; Nicholas T. Seyfried; Tracy L. Young‐Pearse (2022)
Additional file 1: Supplemental Table 1. Differentially expressed proteins in the soluble AD brain proteome. TBS-soluble extracts were prepared from brain tissue described in Table 1, and mass spectrometry used to quantify proteins. Differential expression of individual proteins was analyzed between AD vs. LP-NCI (A) and AD vs. HP-NCI (B). Many more proteins were differentially expressed in the LP-NCI vs. AD comparison than in the HP-NCI vs. AD comparison. Unpaired t-test with Welch correction, two-stage step-up, FDR < 0.05.